Research in the history of economic thought and methodology. Vol. 26, pt. 1 a research annual - Samuels, Warren J., 1933-; Biddle, Jeff; Emmett, Ross B. (Research in the history of economic thought and methodology., 2008)
The collection includes refereed articles on topics in economic methodology and the history of economics, including Austrian economic methodology and Wesley Mitchell.Review essays on new publications cover such topics as Adam Smith, John Kenneth Galbraith, Friedrich Nietzsche, Joseph Schumpeter, Janos Kornai, the Chicago School, French econometrics, financial economics, economic methodology, economists in parliament, the repeal of the Corn Laws, and the role of state power in economics.